2008
DOI: 10.1073/pnas.0802655105
|View full text |Cite
|
Sign up to set email alerts
|

PTEN-deficient cancers depend on PIK3CB

Abstract: Deregulation of the PI3K signaling pathway is observed in many human cancers and occurs most frequently through loss of PTEN phosphatase tumor suppressor function or through somatic activating mutations in the Class IA PI3K, PIK3CA. Tumors harboring activated p110␣, the protein product of PIK3CA, require p110␣ activity for growth and survival and hence are expected to be responsive to inhibitors of its lipid kinase activity. Whether PTEN-deficient cancers similarly depend on p110␣ activity to sustain activatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

24
411
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 486 publications
(439 citation statements)
references
References 41 publications
24
411
4
Order By: Relevance
“…Other studies support that tumors that have loss of PTEN are selectively dependent upon the β-isoform of PI3K (PIK3CB). 64,65 Consistent with this biochemical finding, preclinical studies have shown a positive correlation between loss of PTEN and sensitivity to selective inhibitors of PI3Kβ. 66 Phase I trials of two different PI3K-selective inhibitors are currently enrolling patients (NCT01673737, NCT01458067).…”
Section: Other Targets and Novel Mutations In Cutaneous Melanomasupporting
confidence: 61%
“…Other studies support that tumors that have loss of PTEN are selectively dependent upon the β-isoform of PI3K (PIK3CB). 64,65 Consistent with this biochemical finding, preclinical studies have shown a positive correlation between loss of PTEN and sensitivity to selective inhibitors of PI3Kβ. 66 Phase I trials of two different PI3K-selective inhibitors are currently enrolling patients (NCT01673737, NCT01458067).…”
Section: Other Targets and Novel Mutations In Cutaneous Melanomasupporting
confidence: 61%
“…In addition, however, p110b plays a necessary and positive role in certain tumors driven by PTEN loss (Jia et al 2008;Torbett et al 2008;Wee et al 2008). Similar genetic behavior has previously been noted for the gene encoding the p85 adapter protein (Mauvais-Jarvis et al 2002;Ueki et al 2002Ueki et al , 2003Taniguchi et al 2006); p85 has a dual role as a negative regulator of the ground-state activity of p110 catalytic kinase subunits while also functioning to dock the kinases to activating receptors.…”
Section: Discussionmentioning
confidence: 82%
“…ETS domain-containing transcription factor ERF is a transcription repressor of ETS2 promoter which is regulated by MAPK1/ERK2 phosphorylation (Sgouras et al, 1995). PIK3CB plays a role in phosphatidylinositol (PI) signaling pathway (Wee et al, 2008;Dbouk et al, 2010) through interacting with AKT1, PTEN, and PIK3R1 (Figure 2). Up-regulation of this protein may affect the downstream signaling cascade of PI signaling pathway (Wee et al, 2008), which may promote cancer cell growth and differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…PIK3CB plays a role in phosphatidylinositol (PI) signaling pathway (Wee et al, 2008;Dbouk et al, 2010) through interacting with AKT1, PTEN, and PIK3R1 (Figure 2). Up-regulation of this protein may affect the downstream signaling cascade of PI signaling pathway (Wee et al, 2008), which may promote cancer cell growth and differentiation. Casein kinase (CK) II subunit alpha is involved in cell proliferation.…”
Section: Discussionmentioning
confidence: 99%